2005
DOI: 10.1038/sj.jcbfm.9600054
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Diffusion Changes in Cerebral Hemispheres after MCA Infarcts

Abstract: Diffusion tensor imaging can be used in vivo to assess the longitudinal and regional microstructural changes occurring after middle cerebral artery (MCA) infarcts in humans. Nine patients were investigated 1 week (D7), 1 (M1), 3 (M3), and 6 months (M6) after the occurrence of an isolated MCA infarction. First, an overall analysis was performed using histograms of mean diffusivity (MD) and fractional anisotropy (FA) in each hemisphere. Thereafter, the regional pattern of diffusion changes was investigated voxel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
67
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 48 publications
(50 reference statements)
8
67
0
Order By: Relevance
“…In contrast, 2 studies have reported elevated FA at much later times, namely up to 27 h (Green et al, 2002) and 96 h (Yang et al, 1999). Although averaging all the ROIs for a particular patient showed none with elevated rFA after 7 h in our study, 3% and 18% of individual ROIs from major and subcortical WM tracts showed increased FA values over their homologous contralateral ROI from 9 to 34 h. In the context of human stroke, reductions in FA are more severe at later time points of 2 days to 1 year after onset within the infarct (B40% to 70% decreases) and in regions downstream from the infarct such as the internal capsule, pons, and cerebral peduncles (B8% to 39% decreases) (Buffon et al, 2005;Pierpaoli et al, 2001;Thomalla et al, 2004Thomalla et al, , 2005Werring et al, 2000;Zelaya et al, 1999).…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, 2 studies have reported elevated FA at much later times, namely up to 27 h (Green et al, 2002) and 96 h (Yang et al, 1999). Although averaging all the ROIs for a particular patient showed none with elevated rFA after 7 h in our study, 3% and 18% of individual ROIs from major and subcortical WM tracts showed increased FA values over their homologous contralateral ROI from 9 to 34 h. In the context of human stroke, reductions in FA are more severe at later time points of 2 days to 1 year after onset within the infarct (B40% to 70% decreases) and in regions downstream from the infarct such as the internal capsule, pons, and cerebral peduncles (B8% to 39% decreases) (Buffon et al, 2005;Pierpaoli et al, 2001;Thomalla et al, 2004Thomalla et al, , 2005Werring et al, 2000;Zelaya et al, 1999).…”
Section: Discussionmentioning
confidence: 84%
“…4 It has recently been reported that diffusion tensor imaging (DTI) can detect a signal-intensity change in the ipsilateral pyramidal tract in patients with an ischemic stroke earlier than conventional MR imaging techniques. 5,6 The decrease in the fractional anisotropy (FA) in the involved pyramidal tract becomes progressively reduced during the subacute-to-chronic stages of an ischemic stroke [7][8][9] and correlates with the motor deficit. 7,[10][11][12] With regard to hemorrhagic diseases, a few studies have reported that a change in the FA correlates with the functional outcome, using DTI or diffusion tensor tractography.…”
mentioning
confidence: 99%
“…5,6 The decrease in the fractional anisotropy (FA) in the involved pyramidal tract becomes progressively reduced during the subacute-to-chronic stages of an ischemic stroke [7][8][9] and correlates with the motor deficit. 7,[10][11][12] With regard to hemorrhagic diseases, a few studies have reported that a change in the FA correlates with the functional outcome, using DTI or diffusion tensor tractography. [13][14][15] However, the MR images were obtained at least 3 days after the onset or hematoma removal in these studies, and it is unclear how the FA changes in the very acute phase of ICH or whether the change in the FA in the very acute phase of an ICH correlates with the functional outcome or the motor outcome.…”
mentioning
confidence: 99%
“…Likewise, studies in animal models have shown correspondence between DTI measures and behavioral outcomes (8,10,62). chronic stages after ischemic injury (7,15,32,53). In order to determine whether the decrease in FA we observed in the ipsilateral IC and EC was due to demyelination or loss of axonal fibers, we next determined the axial and radial diffusivity values in each region.…”
Section: █ Discussionmentioning
confidence: 99%
“…These changes too are mostly consistent with reports in other models. Mean diffusivity is commonly elevated during the late sub-acute to chronic stages following stroke (7,15,32,53). Increased radial diffusion is suggestive of demyelination injury (52), as the breakdown of the myelin sheath allows increased diffusion of water perpendicular to the long axis of axonal fibers.…”
mentioning
confidence: 99%